2022
DOI: 10.3390/su142114551
|View full text |Cite
|
Sign up to set email alerts
|

Effect Evaluation of Filling Medium Parameters on Operating and Mechanical Performances of Liquid Heavy Metal Heat Storage Tank

Abstract: In order to evaluate the feasibility and performance of liquid lead-bismuth eutectic as the heat transfer fluid for thermocline heat storage tanks in solar power systems, we conducted an effect evaluation of filling medium parameters on the integrated operating and mechanical performances of a thermocline tank using liquid lead-bismuth eutectic using the computational fluid dynamics simulation method. Four parameters were evaluated: the porosity, thermal conductivity, specific heat capacity, and equivalent dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…31 In further numerical works, the cyclic and standby behavior of a storage system with lead-bismuth and a packed bed with varied filler parameters and properties was theoretically analysed. [32][33][34] Recently, a packed-bed storage system with eutectic lead-bismuth as the heat transfer fluid has been demonstrated on a lab-scale (1 kWh) at KIT. A packed bed of ceramic fillers (zirconium silicate) was used with temperatures of up to 380 C. 35 The results showed that such a system is feasible and performs more efficiently than a single-medium thermocline storage tank with lead-bismuth only.…”
Section: Heavy Liquid Metal Basedmentioning
confidence: 99%
See 3 more Smart Citations
“…31 In further numerical works, the cyclic and standby behavior of a storage system with lead-bismuth and a packed bed with varied filler parameters and properties was theoretically analysed. [32][33][34] Recently, a packed-bed storage system with eutectic lead-bismuth as the heat transfer fluid has been demonstrated on a lab-scale (1 kWh) at KIT. A packed bed of ceramic fillers (zirconium silicate) was used with temperatures of up to 380 C. 35 The results showed that such a system is feasible and performs more efficiently than a single-medium thermocline storage tank with lead-bismuth only.…”
Section: Heavy Liquid Metal Basedmentioning
confidence: 99%
“…48 With a higher storage capacity, a longer discharge of the packed-bed storage can be realized assuming a fixed discharge power. 34 The increase of the packing density could be achieved by either a poly-disperse packed bed or optimized geometrical structures, as discussed in section 4.1.…”
Section: Increase Of Heat Storage Densitymentioning
confidence: 99%
See 2 more Smart Citations